An Insight into the Precise Molecular Interaction and Inhibitory Potential of Amentoflavone and Its Substituted Derivatives on Human α-amylase - Tomisin Happy Ogunwa; Folasade Catherine Ayenitaju (Archives of Current Research International, 2017)
Aims: Biflavonoids have attracted attention of researchers over the last few decades due to their pharmacological activities. Amentoflavone, a biflavonoid considered as apigenin dimer and isolated from various plants, is known for its large range of bioactivities. In the present study, we performed in silico experiment to corroborate the earlier wet experiment, that amentoflavone has anti-diabetic effect via inhibition of α-amylase enzyme. We also evaluated some naturally-occurring substituted derivatives of this compound as potential inhibitors of the enzyme. Methodology: Molecular docking of the ligands on human α-amylase was determined by Vina plugin in PYMOL 1.3 and compared with acarbose, a known inhibitor of the enzyme. Results: Our results showed a high binding affinity (-11.6 kcal/mol) for amentoflavone compared to acarbose (-9.3 kcal/mol) and a reliable configuration on the putative binding site of human a-amylase which can inhibit the enzymatic activity. Molecular analysis results revealed that amentoflavone made hydrophilic interactions with amino acid residues Asp300, Glu233, Asp197, His201 and Gln63 that are critical for catalytic activities of the enzyme. Comparison with its docked monoflavonoid subunit (apigenin) having a lower affinity (-8.9 kcal/mol) and ‘partial’ binding pose validates the possible inhibitory potential for amentoflavone. Some of the substituted derivatives such as bilobetin exhibited different poses within the binding pocket with lower affinity (-11.2 kcal/mol) compared to amentoflavone. The least binding affinity was observed for kayaflavone and heveaflavone with energy value of -9.9 kcal/mol. Conclusion: The results of the current study suggest that amentoflavone inhibits human α-amylase competitively by occupying the substrate binding site and hindering substrate access. Our result is in agreement with the earlier wet experiment on the inhibitory properties of amentoflavone against human α-amylase. Taken together, this work provides insight into the precise molecular interaction of amentoflavone with α-amylase and validates the previous claims that the biflavonoid inhibit the enzyme as part of the mechanism for its antidiabetic activities.